Mediolateral versus lateral episiotomy and their effect on postpartum coital activity and dyspareunia rate 3 and 6 months postpartum - Necesalova, Pavlina; Karbanova, Jaroslava; Rusavy, Zdenek; Pastor, Zlatko; Jansova, Magdalena; Kalis, Vladimir (Sexual & reproductive healthcare, 2016)
OBJECTIVES: Comparison of the effects of two episiotomy types on sexual activity, dyspareunia and overall satisfaction after childbirth. STUDY DESIGN: A prospective follow-up study of a randomized comparative trial evaluating peripartum outcome of a vaginal delivery after mediolateral (MLE) or lateral (LE) episiotomy. MAIN OUTCOME MEASURES: The participants completed questionnaires regarding sexual activity, dyspareunia, perineal pain, aesthetic appearance and overall satisfaction 3 (3M) and 6 months (6M) postpartum. RESULTS: A total of 648 women were available for the analyses (306 MLE, 342 LE). The groups showed no difference regarding resumption and regularity of sex, timing of resumption, frequency and intensity of dyspareunia, perineal pain, aesthetic appearance or overall satisfaction 3M or 6M postpartum. 98.0% of women after MLE and 97.7% after LE resumed sexual intercourse within 6M after delivery (p = 0.74). In the same period 15.6% of women after MLE and 16.1% after LE suffered from considerable dyspareunia (p = 0.86). CONCLUSIONS: Quality of sexual life and perception of perineal pain after MLE is equivalent to LE.
Keywords: dospělí; epiziotomie; průzkumy a dotazníky; Female; Satisfaction; Lateral episiotomy; Prevalence; Adult; mladý dospělý; ženské pohlaví; Postpartum Period; Surveys and Questionnaires; Adolescent; Coital activity; Perineal pain; kvalita života; lidé; porod; Dyspareunia; Parturition; Coitus; následné studie; bolest; prevalence; prospektivní studie; Follow-Up Studies; Prospective Studies; Young Adult; dyspareunie; Mediolateral episiotomy; Pain; Episiotomy; poporodní období; koitus; Quality of Life; mladiství; Humans